Analisis Sentimen Ulasan Aplikasi PeduliLindungi dengan Metode Random Forest - Muhammad Reza Utama Pulungan; Dian Eka Ratnawati; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PeduliLindung is an application developed by the Ministry of Communication and Information (KOMINFO) in collaboration with the Covid-19 Handling Committee. This application is useful for tracing user activities to places visited, getting vaccination info, and also notification of regulations that apply in Indonesia during the Covid-19 pandemic. The PeduliLindung application is used by more than Fifty million users based on information on the total downloads available on the Playstore platform. With many PeduliLindung users during the pandemic, there are often positive, negative and neutral reviews of the PeduliLindung application, especially on the App Store platform. This PeduliLindung application review data will be a data source for analysis and also classifying the sentiment. The PeduliLindung application review data will be obtained using the Scrapping technique where this process can extract data from website pages. The classification method used is Random Forest by testing the depth of the tree and the number of trees. The evaluation methods used are Confusion Matrix. The results of the study with a tree depth of 65 and the number of trees 400 got the best values, namely precision 71%, recall 71%, F1-Score 71% and accuracy 72% with a ratio of 90% training data and 10% test data.